Effective Treatment against ESBL-Producing Klebsiella pneumoniae through Synergism of the Photodynamic Activity of Re (I) Compounds with Beta-Lactams - Iván A. González (MDPI AG, 2021)
Background: Extended-spectrum beta-lactamase (ESBL) and carbapenemase (KPC+) producing Klebsiella pneumoniae are multidrug-resistant bacteria (MDR) with the highest risk to human health. The significant reduction of new antibiotics development can be overcome by complementing with alternative therapies, such as antimicrobial photodynamic therapy (aPDI). Through photosensitizer (PS) compounds, aPDI produces local oxidative stress-activated by light (photooxidative stress), nonspecifically killing bacteria. Methodology: Bimetallic Re(I)-based compounds, PSRe-µL1 and PSRe-µL2, were tested in aPDI and compared with a Ru(II)-based PS positive control. The ability of PSRe-µL1 and PSRe-µL2 to inhibit K. pneumoniae was evaluated under a photon flux of 17 µW/cm2. In addition, an improved aPDI effect with imipenem on KPC+ bacteria and a synergistic effect with cefotaxime on ESBL producers of a collection of 118 clinical isolates of K. pneumoniae was determined. Furthermore, trypan blue exclusion assays determined the PS cytotoxicity on mammalian cells. Results: At a minimum dose of 4 µg/mL, both the PSRe-µL1 and PSRe-µL2 significantly inhibited in 3log10 (>99.9%) the bacterial growth and showed a lethality of 60 and 30 min of light exposure, respectively. Furthermore, they were active on clinical isolates of K. pneumoniae at 3–6 log10. Additionally, a remarkably increased effectiveness of aPDI was observed over KPC+ bacteria when mixed with imipenem, and a synergistic effect from 3 to 6log10 over ESBL producers of K. pneumoniae clinic isolates when mixed with cefotaxime was determined for both PSs. Furthermore, the compounds show no dark toxicity and low light-dependent toxicity in vitro to mammalian HEp-2 and HEK293 cells. Conclusion: Compounds PSRe-µL1 and PSRe-µL2 produce an effective and synergistic aPDI effect on KPC+, ESBL, and clinical isolates of K. pneumoniae and have low cytotoxicity in mammalian cells.